Analysis of Moral Values of Being in The Pursuit of Happyness Movie - Sonia Isabella; Eusabinus Bunau; Eka Fajar Rahmani (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aimed to analyze the moral values representing the educational values presented in the film "The Pursuit of Happyness." The research design employed qualitative descriptives to examine the movie and its script, focusing on scenes and visuals depicting educational values. By observing the protagonist's utterances and actions, the moral values as explained by Linda and Eyre were analyzed. The results of this research revealed five of the six moral values of being, namely honesty (observed in two scenes), courage (manifested in three scenes), peace (seen in four scenes), independence and potential (highlighted in three scenes), and self-discipline and moderation (illustrated in two scenes). These findings provided a valuable resource for students of English education and suggested "The Pursuit of Happyness" as an interesting option for inclusion in educational curricula. The identified moral values could be integrated into teaching and learning, offering teachers a dynamic tool to foster character development. In conclusion, this research underlined the potential of film as a powerful medium for instilling positive values and character. By embracing the moral values embedded in cinematic narratives, educators could contribute to the holistic development of students, emphasizing the important role of character education in forming responsible and moral individuals.